2018
DOI: 10.1002/14651858.cd012528.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Self-management for bronchiectasis

Abstract: There is insufficient evidence to determine whether self-management interventions benefit people with bronchiectasis. In the absence of high-quality evidence it is advisable that practitioners adhere to current international guidelines that advocate self-management for people with bronchiectasis.Future studies should aim to clearly define and justify the specific nature of self-management, measure clinically important outcomes and include children as well as adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 72 publications
0
38
0
4
Order By: Relevance
“…Amongst the subset of participants with bronchiectasis, there was a trend in improvement in mean SGRQ scores for both groups, but this did not meet statistical significance at 6 weeks, 3 or 12 months follow‐up . Although the mean difference in SGRQ scores between the groups exceeded the minimum clinical important difference, the lack of power from the small sample size ( n = 20) means conclusions are unable to be drawn . The authors of the systematic review concluded that there is insufficient evidence to determine if self‐management interventions impact HR‐QoL or exacerbations …”
Section: Self‐management Plansmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst the subset of participants with bronchiectasis, there was a trend in improvement in mean SGRQ scores for both groups, but this did not meet statistical significance at 6 weeks, 3 or 12 months follow‐up . Although the mean difference in SGRQ scores between the groups exceeded the minimum clinical important difference, the lack of power from the small sample size ( n = 20) means conclusions are unable to be drawn . The authors of the systematic review concluded that there is insufficient evidence to determine if self‐management interventions impact HR‐QoL or exacerbations …”
Section: Self‐management Plansmentioning
confidence: 99%
“…A systematic review assessed the efficacy, cost‐effectiveness and adverse effects in self‐management interventions amongst patients with bronchiectasis that included two adult‐based RCT . One was a proof‐of‐concept RCT comparing usual care with an expert patient programme described no differences in SGRQ total scores between the groups post‐intervention, at 3 or 6 months after intervention .…”
Section: Self‐management Plansmentioning
confidence: 99%
See 1 more Smart Citation
“…As of May 2018, a total of 22 systematic reviews examining one or more learning focused interventions for people with respiratory‐related conditions compared to usual care had been published in the Cochrane Database of Systematic Reviews . The patient population groups include adults with asthma (11 reviews), COPD (3 reviews), smoking cessation (2 reviews), cystic fibrosis (1 review), bronchiectasis (1 review), acute upper respiratory tract infections (1 review), lung cancer (1 review), obstructive sleep apnoea (1 review) and tuberculosis (1 review) . The reviews reported two main categories of educational interventions: (i) didactic‐focused teaching for knowledge and (ii) learning experiences for developing self‐management strategies.…”
Section: Impact Of Education Within Prmentioning
confidence: 99%
“…For bronchiectasis, a Cochrane review assessing self-management techniques that included airway clearance techniques, adherence to therapy, exercise or education had insufficient evidence to assess the efficacy of such self-management approaches (205).…”
Section: Self-management Strategiesmentioning
confidence: 99%